Effects of intramuscular morphine in men and women with temporomandibular disorder with myofascial pain. (6th July 2018) - Kang, Soo‐Kyung; Lee, Yeon‐Hee; Park, Hyeji; Ro, Jin Y.; Auh, Q‐Schick
Abstract: Objectives: This placebo‐controlled randomized double‐blinded clinical study assessed the analgesic efficacy of intramuscular morphine in TMD patients with myofascial pain and sex‐dependent responses of the morphine treatment. Subjects and Methods: Men and women with TMD were treated with morphine (1.5 or 5 mg), lidocaine, or saline in the masseter muscle. VAS of pain intensity, PPT, and PPtol were compared between treatment groups and gender. An additional group was treated with morphine in the trapezius muscle to evaluate the systemic effect of morphine that may reduce pain in the masseter muscle. Results: There was a significant difference in VAS scores between the morphine 5 mg group and the saline group favoring morphine, but not between the morphine 5 mg and lidocaine. Morphine 1.5 and 5 mg treatments led to consistently and significantly elevated PPT and PPtol measures in men, but not in women. Morphine administered in the trapezius muscle did not affect the outcome measures. Conclusion: A single dose intramuscular morphine produced analgesic effects up to 48 hr in patients with myofascial pain. Intramuscular morphine elevated mechanical pain threshold and tolerance in the masseter only in male patients, suggesting sex differences in local morphine effects. No systemic effect of intramuscular morphine was detected.